THE INFLUENCE OF GENISTEIN IMPLANTATION ON OFFSPRING SEX RATIOS AND THEIR RELATION TO ESTROGEN LEVELS IN THE BLOOD OF IRAQI CHICKENS - R. A. S. Al-Ghurairi,; W. Kh. A. Al – Hayani,; Y. M. A. Maaeni, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was carried out at the Poultry Research Station / Agricultural Research Department / Ministry of Agriculture, to investigate the effects of implanting genistein (GE) for the period of 1/February/2021 to 16/August/2021. into Iraqi local chickens at various ages on primary (PSF) and secondary (SSF) sex ratios of female, fertility (FE), and hatchability (HA) traits. At the age of 12 weeks, 100 hens and 20 roosters of Iraqi local chickens from the Poultry Research Station were used in this study. After numbering the hens, the birds were housed in individual cages and divided into four treatments (each with 25 chickens) as follows: T1: none implantation; T2, T3, and T4: implantation of 10 mg GE /kg weight at 14, 18, and 22 weeks of age, respectively. The experiment was divided into three periods, each for 28 weeks, and then rated according to the overall average and all of the traits studied. The results showed that implanting GE into hens had a positive influence on FE, PSF, SSF, and estrogen level (ES), especially at 18 weeks of age. There were also significant correlations between traits and ES in hens’ blood. It was also shown that the regression of most traits on ES is first order linear. As a result, it can be concluded that GE has a positive effect on ES, PSF, SSF, with the possibility of predicting sex ratios and sex offspring based on estrogen levels in the blood, and that implantation at 18 weeks of age has produced great results.